Average Ring Current Response to Solar Wind Drivers: Statistical Analysis of 61 Days of ENA Images. Issue 1 (13th January 2022) - Goldstein, J.; Valek, P. W.; McComas, D. J.; Redfern, J.
Abstract: This paper presents the first determination of the average global and regional response of ring current (RC) flux intensity versus four key solar wind (SW) and interplanetary magnetic field (IMF) parameters: SW electric field ( E SW ), IMF polarity ( B Z, IMF ), SW pressure ( P SW ), and SW speed ( V SW ). We analyze energetic neutral atom (ENA) images from Two Wide‐angle Imaging Neutral‐atom Spectrometers (TWINS) to measure the RC response, and use 5‐min downstream‐propagated data from the Advanced Composition Explorer (ACE) and Wind to measure SW driving. Our imaging data comprises 61 events, including 1, 838 global 2D equatorial maps of line‐of‐sight (LOS) averaged ion flux derived from background‐subtracted, 15 min TWINS ENA images spanning 1–30 keV. Average spatial and spectral distributions were organized into four driver strength groups for each SW parameter. E SW has the strongest correlation with RC ion flux (coefficients are [0.95, 0.94, 0.88] at [1, 16, 30] keV, respectively), confirming that magnetospheric convection is a primary driver. In case studies, the global RC responds rapidly (≤15 min) to changes in E SW ranging from strong to weak. P SW is correlated with RC intensity, though not as strongly as E SW, indicating the secondary importance of P SW ‐driven compression in RC injections. Strong E SW increases lower‐energy ions farther eastward and higher‐energy ions closer to midnight, consistent with an energy‐dependent interplay between magnetic drift and convection. The strongest SW driving preferentially increases the least energetic ions, suggesting that quasi‐steady convection can load the nightside RC with cooler ions. Plain Language Summary: This study uses global imaging to obtain the first systematic, empirical determination of the average response to driving by the solar wind of the Earth's ring current, a toroidal region of energetic plasma that encircles the planet in space. Key Points: Solar wind electric field ( E SW ) has the strongest correlation with RC ion flux; magnetospheric convection is a primary driver Strong E SW increases lower‐energy ions farther eastward than higher‐energy ions, because of combined magnetic drift and convection The strongest SW driving preferentially increases the least energetic ions; quasi‐steady convection can load the RC with cooler ions